Enzyme-linked immunosorbent assay to determine the potency of a rotavirus vaccine based on virus-like particles: analytical procedure development and validation - I. E. Filatov; M. M. Silaenkova; V. V. Tsibezov; M. V. Balandina; S. N. Norkina; O. E. Latyshev; O. V. Eliseeva; S. A. Cherepushkin; T. V. Grebennikova (Биопрепараты: Профилактика, диагностика, лечение)
INTRODUCTION. Rotavirus vaccines based on virus-like particles (VLPs), non-infectious recombinant proteins of human rotavirus A that mimic the structure of the native virus, show promise for preventive vaccination. Presumably, the optimal method to determine the potency of VLP-based rotavirus vaccines is the enzyme-linked immunosorbent assay (ELISA) method used to measure the titre of specific IgG antibodies to rotavirus A proteins in serum samples from vaccinated animals.AIM. This study aimed at assessing the potency of a VLP-based rotavirus vaccine by developing and validating an analytical procedure using ELISA to determine the levels of antibodies to the VP2 and VP6 proteins of rotavirus A in serum samples from vaccinated guinea pigs.MATERIALS AND METHODS. The potency of the VLP-based rotavirus vaccine was determined in vivo in three types of experimental animals, including BALB/c mice, agouti guinea pigs, and newborn minipigs. The animals received three intramuscular injections of the vaccine at a dose of 30 µg. This study used the indirect ELISA method to quantify VP2- and VP6-specific immunoglobulin G (IgG) antibodies and the virus-neutralisation test to measure neutralising antibodies (nAbs) to rotavirus A in animal serum samples. The study involved calculating the geometric mean titres (GMTs) of antibodies. The authors validated the analytical procedure for potency assessment on two batches of the vaccine using standard statistical analysis methods.RESULTS. The study compared VP2- and VP6-specific IgG and nAb levels 14 days after the first, second, and third vaccinations. The authors observed a significant increase in antibody titres and statistically significant (p<0.05) differences between groups as early as after the second vaccination. Double vaccination induced rotavirus-specific IgGs and nAbs in newborn minipigs (GMTs of 200.0 and 108.9, respectively) and guinea pigs (GMTs of 12,800 and 2,600, respectively). Vaccinated mice demonstrated a significant increase in rotavirus-specific IgG levels (GMT of 572,440). Guinea pigs were selected as a relevant model for validating the ELISA-based potency assessment procedure. The validation study used a double vaccination scheme. The validation using two batches of the VLP-based rotavirus vaccine indicated that the ELISA-based analytical procedure met the acceptance criteria for specificity, repeatability, and intermediate precision. The repeatability assessment resulted in a coefficient of variation (CV) of 12.4% for batch 1 and a CV of 7.7% for batch 2, whereas the intermediate precision assessment showed a CV of 6.9% for batch 1 and a CV of 10.2% for batch 2, which were within the acceptance criteria for both validation parameters (CV≤15%).CONCLUSIONS. The authors developed and validated an ELISA-based analytical procedure for assessing the potency of VLP-based preventive rotavirus vaccines. According to the study results, ELISA is applicable to the control of the potency of VLP-based preventive rotavirus vaccines.